Sabbatical project: a Norton critical edition of W. D. Howell's novel, The rise of Silas Lapham (1885) - Petrie, Paul R. (2017)
Keywords: dept.eng; faculty_collection; sabbatical_report

Challenging evaluation: The complexity of grading writing in hybrid MOOCs - McEachern, R.W. (Handb. of Res. on Writ. and Compos. in the Age of MOOCs, 2017)
When MOOCs exploded into the public consciousness in 2012, many supporters touted their potential to disrupt higher education. In a short time, MOOCs have evolved, and that role as radical change agents seems to have faded. However, the use of Hybrid MOOCs, in which onground courses use MOOCs for some or all of their content, does have the potential to be disruptive, albeit on a smaller scale. This article will describe one Hybrid MOOC and the ways it could be used to disrupt individual pedagogy, and perhaps affect larger change as a result. © 2017 by IGI Global. All rights reserved.
Journal Abbreviation: Handb. of Res. on Writ. and Compos. in the Age of MOOCs
Keywords: dept.eng

Can we be part of the pride? Reading animals through comics in the undergraduate classroom - Baraw, Charles; Smyth, Andrew (Animal comics: Multispecies storyworlds in graphic narratives, 2017)
Animal characters abound in graphic narratives ranging from Krazy Kat and Maus to WE3 and Terra Formars. Exploring these and other multispecies storyworlds presented in words and images, Animal Comics draws together work in comics studies, narrative theory, and cross-disciplinary research on animal environments and human-animal relationships to shed new light on comics and graphic novels in which animal agents play a significant role. At the same time, the volume's international team of contributors show how the distinctive structures and affordances of graphic narratives foreground key questions about trans-species entanglements in a more-than-human world. The writers/artists covered in the book include: Nick Abadzis, Adolpho Avril, Jeffrey Brown, Sue Coe, Matt Dembicki, Olivier Deprez, J. J. Grandville, George Herriman, Adam Hines, William Hogarth, Grant Morrison, Osamu Tezuka, Frank Quitely, Yu Sasuga, Charles M. Schultz, Art Spiegelman, Fiona Staples, Ken'ichi Tachibana, Brian K. Vaughan, and others.
Google-Books-ID: 8rU7DwAAQBAJ
Keywords: Art / Subjects & Themes / Landscapes & Seascapes; Comics & Graphic Novels / Literary; Humor / Form / Comic Strips & Cartoons; Literary Criticism / Comics & Graphic Novels; dept.eng

Spleen elegy - Labbe, Jason (BlazeVOX [books], 2017)
Let’s twin and twine together two primary aspects of how America can see herself—the good atoms of Whitman’s leaves of grass, and the engines humming their freedom on the highways that cut across those 19th century fields. Now, Jason Labbe well knows, as Whitman’s atoms become pixels, we find ourselves at a crossroads, learning again and again the consequences of “the indescribable way you shape / a past of little use.” Seeking to find that law or logic to shattering, be it in the memory-echo of personal trauma caught on infinite loop in the mind, or be it the dismal virtualities of the post-modern ether, the poems of Spleen Elegy unfold their rueful nostalgia: “I have something accurate to say that lacks perspective.” That may well be the very accuracy we most need, riding the routes of America, the byways and frontage roads, seeking anyone who is willing for a poem or two to see. —Dan Beachy-Quick "A chunk of broken tar”—that's the color of this book. And the sound of this book is "a train in the static." Its poems count time in "decaseconds of dusk." To read this book is to feel the uneasy passivity and unerring stuckness, the particular absurdity, of certain citizens stuck in this millennium. So many lines made me laugh. And sigh. But not cry. Jason Labbe is great at melancholy. Baudelaire's mosquito is definitely here: "I am Past / who passing lit and sucked your life and left." The future is unthinkable and unalterable. Except. Except! Lucretius' swerve is also here. Atoms may veer randomly, which is extra significant in a book that takes place mostly on the road. "My sutures are beautiful as a tread pattern," he says, and it is easy (and dangerous) to fall in love with Labbe's strangled version of optimism. —Darcie Dennigan
Keywords: dept.eng

Foucault, confession, and Donne - Dodson, Joel M. (Forms of faith, 2017)
Keywords: dept.eng

Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex - Larocco, Steve (Exploring Empathy, 2017)
"Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex" published on 01 Jan 2017 by Brill | Rodopi.
Keywords: dept.eng

Hawthorne, a pilgrimage to Salem, and the poetics of literary tourism - Baraw, Charles (Canadian Review of American Studies, 2017)
From the 1830s to the end of his career, Nathaniel Hawthorne used the tropes of aesthetic tourism to call out, or interpellate, the reader as a literary tourist. In many cases, Hawthorne’s focalizi...
2 citations (Crossref) [2023-10-31]
Keywords: "Alice Doane's appeal" Caroline Gilman; Literary tourism; Narrative poetics; Nathaniel Hawthorne; Samuel Gilman; Touristic poetics; dept.eng